2016
DOI: 10.1111/adb.12459
|View full text |Cite
|
Sign up to set email alerts
|

A hypo‐status in drug‐dependent brain revealed by multi‐modal MRI

Abstract: Drug addiction is a chronic brain disorder with no proven effective cure. Assessing both structural and functional brain alterations using multimodal, rather than purely unimodal imaging techniques, may provide a more comprehensive understanding of the brain mechanisms underlying addiction, which in turn may facilitate future treatment strategies. However, this type of research remains scarce in the literature. We acquired multi-modal MRI from 20 cocaine-addicted individuals and 19 age-matched controls. Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…Another region affected by chronic cocaine SA that has been implicated in reward-related behavior is the amygdala. Prior neuroimaging studies have demonstrated that amygdala volume in cocaine users is significantly smaller than that of matched control subjects ( Makris et al, 2004 ) and that reductions in amygdala cerebral blood flow are correlated with greater cocaine dependence ( Wang et al, 2017 ). Consistent with these findings in humans, cocaine self-administration causes a decrease in amygdala glucose metabolism in both rats and nonhuman primates ( Macey et al, 2004 ; Beveridge et al, 2006 ; Calipari et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another region affected by chronic cocaine SA that has been implicated in reward-related behavior is the amygdala. Prior neuroimaging studies have demonstrated that amygdala volume in cocaine users is significantly smaller than that of matched control subjects ( Makris et al, 2004 ) and that reductions in amygdala cerebral blood flow are correlated with greater cocaine dependence ( Wang et al, 2017 ). Consistent with these findings in humans, cocaine self-administration causes a decrease in amygdala glucose metabolism in both rats and nonhuman primates ( Macey et al, 2004 ; Beveridge et al, 2006 ; Calipari et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“… Moderate Neurodegeneration Wang et al. [38] Substance misuse 39 (cocaine addict 20/healthy controls 19). Cocaine addict: 42.15 (4.3)/NA.…”
Section: Resultsmentioning
confidence: 99%
“…In a multimodal MRI study, Wang et al. [38] identified hypoperfusion in the prefrontal cortex, anterior cingulate cortex, insula, right temporal cortex, and dorsolateral prefrontal cortex in cocaine addicts compared with controls.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 55.8-80% (2,3) of patients relapsed to heroin use after being abstinent from drug use for 1-3 years at a 12-month follow-up. A major reason for the lack of an effective method for preventing relapse is the lack of a clear picture of heroin addiction-related brain mechanisms (4).…”
Section: Introductionmentioning
confidence: 99%